Aetiology and Statistics in Cleft Lip and Palate - Dr. J. L. Gupta; Dr. S. K. Bhatnagar; Dr. J. L. Srivastava (Indian Journal of Plastic Surgery)
1. 1326 cases have been seen during the last ten years (1963-1973) in the department of Burns, Plastic and Maxillofacial Surgery. Safdarjung Hospital, New Delhi-16.